Traditional Procurement versus Public-Private Partnership: A Comparison and Synergies with Focus on Cross-Border Contracts - Ludmila Štěrbová; Jaroslav Halík; Pavla Neumannová (Naše gospodarstvo/Our economy, 2020)
Government purchases represent an important part of the world economy. Selling to the public sector is a key business activity for certain industries or service providers. The public procurement segment’s attractiveness is also underlined by the security of payment and large extent of supplies. With globalisation as a worldwide phenomenon, businesses do not have to rely only on domestic institutions; they can enter international B2G markets as well. However, the ability of private companies to do business with foreign governments is limited by various national legislations as governments settle the procurement regulation with respect to their national interests. In the following overview article, the authors analyse the two main and typical procurement types – traditional procurement and public-private partnership – with regard to recent development trends, international regulatory framework, opportunities and barriers to entry for European businesses.The main goal of the paper is to define, based on this analysis, the main differences and possible synergies of the traditional procurement and public-private partnership while focusing on cross-border contracts. This paper can be regarded as useful for business, academia as well as the public sector.